Public Trust and the Legal Validity of Electronic Signatures in Indonesia - Lahangatubun, Nurjana; Muliyono, Andi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The advancement of digital technology has accelerated the adoption of electronic signatures (ETS) in a wide range of civil transactions in Indonesia. However, their legal validity and evidentiary strength continue to present significant challenges. This study seeks to examine the legal foundations governing the validity of ETS within the framework of Indonesian civil law, evaluate their recognition as admissible evidence in judicial proceedings, and identify key implementation barriers related to technical infrastructure, procedural limitations, and public trust. Employing a normative legal approach combined with jurisprudential analysis of court decisions from 2018 to 2025, the study finds that while certified ETS are normatively recognized as legally valid, their practical application remains inconsistent—particularly in cases involving uncertified ETS. The primary impediments include limited technical capacity among law enforcement personnel, low levels of digital literacy, and uneven access to certification infrastructure. In conclusion, the effective implementation of ETS in Indonesia requires regulatory harmonization, capacity-building within judicial institutions, and efforts to strengthen public confidence in the legal validity and security of ETS within the national legal system.